Fabrication of Fe3O4/PEG 4000/Oleic Acid Ferrofluids on Crystal Structure and Magnetic Properties Using Rhee Sumbawa Iron Sand - Bahtiar, Syamsul; Islam, Izzul; Jayatri, Adella Ulyandana; Widyawati, Fauzi; Yanuar, Emsal (Jurnal Pijar Mipa, 2025)
The fabrication of ferrofluid using Fe3O4 nanoparticles synthesized from Rhee Sumbawa iron sand has been successfully carried out. This fabrication was conducted to study the crystal structure characteristics and magnetic properties of the ferrofluid from Rhee iron sand. The fabrication used the co-precipitation method at room temperature to synthesise Fe3O4 nanoparticles. In contrast, the ferrofluid fabrication employed a magnetic stirrer with the addition of PEG 4000/Oleic Acid as a surfactant. The structure and magnetic characteristics of the Fe3O4/PEG 4000/AO ferrofluid will be investigated in this work. The results of the XRF characterization show an Fe content of 91.73%, indicating that the purity of Fe has been successfully increased using a permanent magnet separation method. The XRD characterization results show the formation of a cubic crystal system with lattice parameters a=b=c = 9.3797 Å, α=β=γ = 90°, and the crystal size obtained from the refinement is 8.42 nm. The TEM characterization results indicate that the morphology of the nanoparticles is spherical with a particle size of 7.34 nm. The VSM characterization results obtained the ferrofluid magnetization value in the 0.08–0.34 emu/g range.